Walter Benjamin : overpowering conformism - Leslie, Esther, 1964- (Pluto Press, 2000)
Esther Leslie's path-breaking study of Walter Benjamin is unlike any other book presently available in English on Benjamin, in seeking to make a case for a more politicised reading of Benjamin's oeuvre. In looking at the entirety of Benjamin's work - rather than the four or five essays available in English which tend to form the Benjamin 'canon' - Leslie offers powerful new insights into a key twentieth-century political thinker, correcting the post-structuralist bias that has characterised so much Benjamin scholarship, and repositioning Benjamin's work in its historical and political context. In her examination of Benjamin's commentary on the politics and aesthetics of technology - from Benjamin's work on nineteenth-century industrial culture to his analyses of the Nazi deployment of the bomber - Esther Leslie recontextualises Benjamin's writings in a lucid and cogently argued new study.
Keywords: Benjamin, Walter, -- 1892-1940 -- Political and social views.; Benjamin, Walter, -- 1892-1940 -- Pensée politique et sociale.; Benjamin, Walter, -- 1892-1940; Benjamin, Walter, -- 1892-1940.; Benjamin, Walter.; LITERARY CRITICISM -- European -- German.; POLITICAL SCIENCE -- Political Ideologies -- Democracy.; Political and social views; Filosofie.; German prose literature -- 20th century -- History and criticism.; Political scientists -- Germany.